A kind of polyamide 66 resin and preparation method thereof

By using specific catalysts and stabilizers during the polymerization process of polyamide 66, the polymerization reaction is regulated, and the problems of poor dimensional stability, high water absorption and poor high temperature resistance in applications are solved, and the high temperature resistance and lubricity of polyamide 66 resin are improved, and its injection molding processing performance is improved.

CN116144172BActive Publication Date: 2025-03-04HUAFON GROUP
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111399076.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-19
Publication Date
2025-03-04
Estimated Expiration
2041-11-19

AI Technical Summary

Technical Problem

In the prior art, the polymerization process of polyamide 66 has not been studied in depth, resulting in poor dimensional stability, high water absorption and poor high temperature resistance in its application, which limits its wide application in different fields.

Method used

Through the combination of the first catalyst and the second catalyst, the polymerization process of the polyamide 66 is regulated, and through the combination of the stabilizer and the lubricant, a polyamide 66 resin with good high temperature resistance and lubricity is prepared, which improves its injection molding processing performance.

Benefits of technology

The high temperature resistance and lubricity of polyamide 66 resin are improved, and its injection molding processing performance is improved, ensuring that high tensile strength and fluidity can be maintained at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003364280140000141
    Figure BDA0003364280140000141
Patent Text Reader

Abstract

The present invention provides a polyamide 66 resin and a preparation method thereof. The polyamide 66 resin comprises the following components in parts by weight: 100 parts of polyamide 66, 0.0002-0.01 parts of a stabilizer and 0.0005-0.005 parts of a lubricant; the polyamide 66 comprises the following raw material components in parts by weight: 115 parts of polyamide 66 salt, 0.0001-0.002 parts of a first catalyst and 0.00034-0.0014 parts of a second catalyst; the first catalyst is selected from any one of sodium bicarbonate, potassium bicarbonate or sodium carbonate or a combination of at least two; the second catalyst is selected from sodium hypophosphite and / or acetic acid. The polyamide 66 resin provided by the present invention has good high temperature resistance, lubricity and fluidity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polyamide resins, and in particular relates to a polyamide 66 resin and a preparation method thereof. Background Art

[0002] Nylon 66 resin (polyhexamethylene adipamide, referred to as polyamide 66) is a widely used engineering plastic. Because its molecular chain contains highly polar amide groups (-CONH-), the hydrogen bonds formed between the groups make the structure of PA66 easy to crystallize, so that the material has excellent mechanical properties, self-lubrication, wide operating temperature, good electrical insulation, good oil resistance and chemical stability, easy processing and other characteristics. Therefore, it is widely used in the fields of automotive parts, mechanical parts, electronic appliances, adhesives and packaging materials. However, due to its poor dimensional stability, high water absorption and poor high temperature resistance, the application of nylon 66 is limited. Therefore, how to obtain a polyamide 66 with excellent mechanical properties and excellent chemical properties has become a research hotspot.

[0003] CN101440215A discloses an ultra-high toughness polyamide 66 material, which is made of the following raw materials in weight ratio: 50-70% nylon, 5-10% compatibilizer, 1-30% styrene rubber, 10-30% talcum powder, and 0.1-1% antioxidant; the compatibilizer is a grafted polymerized oligomer of styrene rubber grafted with unsaturated acid or anhydride, and the grafting rate is 0.5-1%. The preparation method is as follows: weigh the raw materials according to weight percentage; put all the raw materials into a high-speed mixer and mix for 5-8 minutes; discharge the materials; put the mixed raw materials into a screw machine for extrusion and granulation, and the speed of the screw machine is 180-600 rpm and the temperature is 240-250°C. This technical solution uses a new type of compatibilizer and cooperates with advanced formula design to prepare a new type of ultra-high toughness polyamide 66 material, which can be widely used in the fields of automobiles, electronics and electrical engineering, and construction engineering.

[0004] CN102516761A discloses a hydrolysis and alcoholysis resistant nylon 66 composite material and a preparation method thereof. The hydrolysis and alcoholysis resistant nylon 66 composite material comprises, by weight, 51.8 to 84.5 parts of nylon resin, 15 to 40 parts of chopped glass fibers, 0.1 to 0.6 parts of nucleating agents, 0.1 to 0.6 parts of thermal stabilizers, 0.1 to 1.0 parts of alcoholysis resistant additives, 0.1 to 5 parts of barriers, and 0.1 to 1.0 parts of lubricants. The preparation method comprises: uniformly mixing the pre-dried nylon 66 resin, antioxidant, hydrolysis resistant agent, barrier, nucleating agent, and lubricant at high speed; feeding the above mixture and glass fibers into a twin-screw extruder for extrusion granulation. This technical solution adds various additives to the glass fiber reinforced nylon 66 composite material to improve the crystallinity of the material, increase the stability of the polyamide macromolecules during processing and long-term use, improve the interfacial bonding strength between the glass fiber and the matrix resin, and other means to give the glass fiber reinforced nylon 66 better long-term resistance to erosion by ethylene glycol aqueous solution and long-term thermal oxidation stability.

[0005] CN101608065A discloses a halogen-free, environmentally friendly, flame-retardant, reinforced nylon 66 resin and a preparation method thereof, wherein the weight percentage of polyamide 66 is 30.0-63.0%, and the weight percentage of alkali-free long glass fiber is 20.0-35.0%; the components and their weight percentages are as follows: 2.0-10.0% of maleic anhydride grafted compatibilizer, 0.5-3.0% of vinyl fluorine resin, 0.4-1.0% of hindered phenol antioxidant, 0.2-2.0% of pentaerythritol stearate, 0.2-1.0% of a mixture of copper salt and halogen compound, and at least one of aluminum hypophosphite and melamine phosphate, up to 16.0%. In this technical solution, by adopting compatibilization technology and blending technology, the stress that can be tolerated can be significantly increased, and its toughness can be effectively improved; the thermal stability can also be significantly improved, with a higher heat deformation temperature and oxygen index, and improved comprehensive mechanical properties.

[0006] As can be seen from the above content, most of the prior art uses additives to improve the performance of polyamide 66 so that it meets the requirements of use in different fields, but there is no in-depth study on the polymerization process of polyamide 66. Therefore, how to obtain a polyamide 66 resin with excellent performance by controlling the polymerization process of polyamide 66 and using appropriate additives has become a technical problem that needs to be solved urgently. Summary of the invention

[0007] In view of the shortcomings of the prior art, the object of the present invention is to provide a polyamide 66 resin and a preparation method thereof. The present invention regulates the polymerization process of polyamide 66 by using a first catalyst and a second catalyst in combination, and prepares a polyamide 66 resin with good high temperature resistance and lubricity by using a stabilizer and a lubricant in combination, thereby improving the injection molding processing performance of the polyamide 66 resin.

[0008] To achieve this object, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a polyamide 66 resin, wherein the polyamide 66 resin comprises the following components in parts by weight:

[0010] 100 parts of polyamide 66, 0.0002-0.01 parts of stabilizer and 0.0005-0.005 parts of lubricant;

[0011] The polyamide 66 comprises the following raw material components in parts by weight:

[0012] 115 parts of polyamide 66 salt, 0.0001-0.002 parts of the first catalyst and 0.00034-0.0014 parts of the second catalyst;

[0013] The first catalyst is selected from any one or a combination of at least two of sodium bicarbonate, potassium bicarbonate or sodium carbonate;

[0014] The second catalyst is selected from sodium hypophosphite and / or acetic acid.

[0015] The present invention selects a specific type of catalyst and uses a first catalyst and a second catalyst in combination to regulate the polymerization process of polyamide 66, and uses a stabilizer and a lubricant in combination to prepare a polyamide 66 resin with good high temperature resistance and lubricity, thereby improving the injection molding processing performance of the polyamide 66 resin.

[0016] In the present invention, the first catalyst is a weakly alkaline inorganic salt, specifically any one of sodium bicarbonate, potassium bicarbonate or sodium carbonate, or a combination of at least two thereof. Under the catalysis of the weakly alkaline inorganic salt, the amide bond will slowly hydrolyze, thereby breaking the molecular chain of polyamide 66 and reducing its molecular weight, thereby achieving the purpose of regulating the molecular weight. The second catalyst is sodium hypophosphite and / or acetic acid, wherein sodium hypophosphite is a weakly acidic compound, which can play a catalytic and viscosity-increasing role in the polymerization process of polyamide 66, promote intermolecular dehydration and molecular chain growth, and acetic acid can react with carboxyl groups to regulate the catalytic effect of sodium hypophosphite.

[0017] In the present invention, the weight proportion of the stabilizer can be 0.0002 parts, 0.0005 parts, 0.001 parts, 0.002 parts, 0.003 parts, 0.004 parts, 0.005 parts, 0.006 parts, 0.007 parts, 0.008 parts, 0.009 parts or 0.01 parts, etc.

[0018] The weight proportion of the lubricant may be 0.0005, 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045 or 0.005, etc.

[0019] The weight proportion of the first catalyst may be 0.0001 part, 0.0002 part, 0.0004 part, 0.0008 part, 0.001 part, 0.0012 part, 0.0014 part, 0.0016 part, 0.0018 part or 0.002 part, etc.

[0020] The weight proportion of the second catalyst may be 0.00034, 0.0004, 0.0005, 0.0006, 0.0007, 0.0008, 0.0009, 0.001, 0.0011, 0.0012, 0.0013 or 0.0014, etc.

[0021] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0022] As a preferred technical solution of the present invention, the second catalyst is a combination of sodium hypophosphite and acetic acid.

[0023] Preferably, the weight proportion of the sodium hypophosphite is 0.00004 to 0.0002 parts, for example, it can be 0.00004 parts, 0.00006 parts, 0.00008 parts, 0.0001 parts, 0.00012 parts, 0.00014 parts, 0.00016 parts, 0.00018 parts or 0.0002 parts, etc.

[0024] Preferably, the weight proportion of the acetic acid is 0.0003 to 0.0012 parts, for example, it can be 0.0003 parts, 0.0004 parts, 0.0005 parts, 0.0006 parts, 0.0007 parts, 0.0008 parts, 0.0009 parts, 0.001 parts, 0.0011 parts or 0.0012 parts.

[0025] In the present invention, by selecting a combination of sodium hypophosphite and acetic acid as the second catalyst and controlling the weight fractions of the two within a specific range, the prepared polyamide 66 resin has good physical properties and processing properties. If only sodium hypophosphite is used as the second catalyst, its catalytic effect will cause the molecular chain to continue to grow during the secondary heating, ultimately affecting the fluidity of the product and causing processing difficulties; if only acetic acid is used as the second catalyst, the polymerization reaction rate will be too slow, and even a high polymer cannot be formed, affecting product performance.

[0026] As a preferred technical solution of the present invention, the stabilizer is selected from copper salt stabilizers and / or hindered amine stabilizers.

[0027] Preferably, the copper salt stabilizer is selected from inorganic copper salt stabilizers and / or organic copper salt stabilizers.

[0028] Preferably, the inorganic copper salt stabilizer is selected from any one or a combination of at least two of copper acetate, cuprous iodide, copper bromide, copper nitrate, potassium iodide or potassium bromide.

[0029] Preferably, the organic copper salt stabilizer is selected from any one of Brueggemann H3386 stabilizer, Brueggemann H3336 stabilizer or Brueggemann TP-H1606 stabilizer, or a combination of at least two thereof.

[0030] It should be noted that the manufacturer of the Brüggemann H3386 stabilizer, the Brüggemann H3336 stabilizer or the Brüggemann TP-H1606 stabilizer in the present invention is Brüggemann of Germany.

[0031] Preferably, the hindered amine stabilizer is selected from any one of Clariant TFB117, light stabilizer 5591 or light stabilizer 944, or a combination of at least two thereof.

[0032] It should be noted that the manufacturer of the light stabilizer 5591 in the present invention is Xinxiu Chemical; the manufacturer of the light stabilizer 944 is Beijing Tiangang.

[0033] Preferably, the stabilizer is a combination of a copper salt stabilizer and a hindered amine stabilizer.

[0034] Preferably, the weight proportion of the copper salt stabilizer is 0.0001 to 0.005 parts, for example, it can be 0.0001 parts, 0.0005 parts, 0.001 parts, 0.0015 parts, 0.002 parts, 0.0025 parts, 0.003 parts, 0.0035 parts, 0.004 parts, 0.0045 parts or 0.005 parts, etc.

[0035] Preferably, the weight proportion of the hindered amine stabilizer is 0.0001 to 0.005 parts, for example, it can be 0.0001 parts, 0.0005 parts, 0.001 parts, 0.0015 parts, 0.002 parts, 0.0025 parts, 0.003 parts, 0.0035 parts, 0.004 parts, 0.0045 parts or 0.005 parts, etc.

[0036] In the present invention, by selecting a combination of a copper salt stabilizer and a hindered amine stabilizer as a stabilizer and controlling the weight fractions of the two within a specific range, the prepared polyamide 66 resin has good high temperature resistance through the synergistic effect between the two. If only a copper salt stabilizer or a hindered amine stabilizer is used, the prepared polyamide 66 resin has poor high temperature resistance.

[0037] As a preferred technical solution of the present invention, the lubricant is selected from any one of oleamide, erucamide, stearyl erucamide, aluminum stearate, aluminum distearate, zinc stearate or magnesium stearate, or a combination of at least two thereof.

[0038] As a preferred technical solution of the present invention, the polyamide 66 resin also includes 0.0001 to 0.005 parts of a fluidity improver, for example, 0.0001, 0.0002, 0.0003, 0.0005, 0.001, 0.0015, 0.002, 0.0025, 0.003, 0.0035, 0.004, 0.0045 or 0.005, etc.

[0039] Preferably, the fluidity improver is selected from any one of ethylene bisstearamide, hyperbranched polyamide polyester HyPerHPN202, montan wax or rice bran wax, or a combination of at least two thereof.

[0040] As a preferred technical solution of the present invention, the preparation method of polyamide 66 is as follows:

[0041] The first catalyst and the second catalyst are mixed with water to obtain a mixed solution, and the mixed solution is mixed with polyamide 66 salt to carry out a polymerization reaction to obtain polyamide 66.

[0042] As a preferred technical solution of the present invention, the mass percentage of the first catalyst in the mixed liquid is 5-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0043] Preferably, the mass percentage of the second catalyst in the mixed liquid is 5-20%, for example, it can be 2%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%, etc.

[0044] It should be noted that the second catalyst is preferably a combination of sodium hypophosphite and acetic acid, wherein the mass percentage of sodium hypophosphite in the mixed solution is 0.5-3% (for example, it can be 0.5%, 1%, 1.5%, 2%, 2.5% or 3%, etc.), and the mass percentage of acetic acid in the mixed solution is 4-17% (for example, it can be 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16% or 17%, etc.).

[0045] As a preferred technical solution of the present invention, the specific method of the polymerization reaction is as follows:

[0046] The reaction system after the mixed solution and the polyamide 66 salt are mixed is concentrated at 150-155° C. (for example, 150° C., 151° C., 152° C., 153° C., 154° C. or 155° C.) and 0.25 MPa for 50-60 min (for example, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min), and then the pressure is increased to 1.75-1.85 MPa (for example, 1.75 MPa, 1.77 MPa, 1.79 MPa, 1.81 MPa, 1.83 MPa or 1.85 MPa, etc.), maintain the pressure for 50-60 min (for example, 50 min, 52 min, 54 min, 56 min, 58 min or 60 min, etc.), when the temperature of the reaction system reaches 265-267°C (for example, 265°C, 266°C or 267°C, etc.), within 40-60 min (for example, 40 min, 42 min, 45 min, 47 min, 50 min, 52 min, 55 min, 57 min or 60 min, etc.), release the pressure of the reaction system to 0 MPa, and within 2-10 min (for example, 2 min, 4 min, 6 min, 8 min or 10 min, etc.), evacuate the reaction system to -0.01 to -0.03 MPa (for example, -0.01 MPa, 0.015 MPa, -0 .02MPa, -0.025MPa or -0.03MPa, etc.), when the temperature of the reaction system reaches 270-275°C (for example, it can be 270°C, 271°C, 272°C, 273°C, 274°C or 275°C, etc.), the pressure is increased to 0.2-0.6MPa (for example, it can be 0.2MPa, 0.3MPa, 0.4MPa, 0.5MPa or 0.6MPa, etc.), and the polymerization reaction is completed to obtain the polyamide 66.

[0047] It should be noted that the present invention also includes a post-processing step, and the post-processing method is: pelletizing the obtained polyamide 66.

[0048] In a second aspect, the present invention provides a method for preparing the polyamide 66 resin as described in the first aspect, the preparation method comprising the following steps:

[0049] The polyamide 66 resin is obtained by mixing polyamide 66 with a stabilizer, a lubricant and an optional fluidity improver through a screw extruder and then pelletizing.

[0050] As a preferred technical solution of the present invention, the operating temperature of the screw extruder is 265-330°C, for example, it can be 265°C, 270°C, 280°C, 290°C, 300°C, 310°C, 320°C or 330°C.

[0051] Compared with the prior art, the present invention has the following beneficial effects:

[0052] The present invention regulates the polymerization process of polyamide 66 by using a first catalyst and a second catalyst in combination, and prepares a polyamide 66 resin with good high temperature resistance and lubricity by using a stabilizer, a lubricant and a fluidity improver in combination, thereby improving the injection molding processing performance of the polyamide 66 resin. After heat treatment at 180°C for 72 hours, the tensile strength can still be maintained at more than 80MPa, which is 81.9-86.8MPa; the melt index is greater than 87g / 10min, which is 87-93g / 10min; the relative viscosity can reach 2.66-2.67; the number of demoulding roots is 85-100, and the maximum processing temperature is 280-285°C. DETAILED DESCRIPTION

[0053] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0054] The sources of some components in the embodiments and comparative examples are as follows:

[0055] Hyperbranched polyamide polyester HyPer HPN202: Wuhan Hyperbranched Resin Technology Co., Ltd.;

[0056] Montan wax: Clariant CaV102;

[0057] Rice bran wax: Clariant RBW360;

[0058] Light stabilizer 5591: Xinxiu Chemical;

[0059] Brüggemann H3386 stabilizer: Brüggemann, Germany;

[0060] Light stabilizer 944: Beijing Tiangang.

[0061] Example 1

[0062] This embodiment provides a polyamide 66 resin and a preparation method thereof. The polyamide 66 resin includes the following components in parts by weight:

[0063] 100 parts of polyamide 66, 0.003 parts of copper acetate, 0.002 parts of Clariant TFB117 stabilizer, 0.002 parts of oleamide and 0.001 parts of ethylene bis stearamide;

[0064] The polyamide 66 comprises the following raw material components in parts by weight:

[0065] 115 parts of polyamide 66 salt, 0.001 parts of sodium bicarbonate, 0.0001 parts of sodium hypophosphite and 0.001 parts of acetic acid;

[0066] The preparation method of polyamide 66 is as follows:

[0067] Sodium bicarbonate, sodium hypophosphite, acetic acid and water are mixed to obtain a mixed solution, and the mixed solution is mixed with polyamide 66 salt, concentrated at 155° C. and 0.25 MPa for 60 minutes, and then the pressure is increased to 1.75 MPa and maintained for 60 minutes. When the temperature of the reaction system reaches 266° C., the pressure of the reaction system is released to 0 MPa at 50 minutes, and then the reaction system is evacuated to -0.02 MPa within 10 minutes. When the temperature of the reaction system reaches 275° C., the pressure is increased to 0.4 MPa to complete the polymerization reaction, and pelletized to obtain the polyamide 66; wherein the mass percentage of the first catalyst in the mixed solution is 5%, the mass percentage of the sodium hypophosphite is 0.5%, and the mass percentage of the acetic acid is 5%.

[0068] The preparation method of the above polyamide 66 resin is as follows:

[0069] The polyamide 66 resin is obtained by mixing polyamide 66, copper acetate, Clariant TFB117 stabilizer, oleamide and ethylene bisstearamide through a screw extruder and then pelletizing. The operating temperature of the screw extruder is 280°C.

[0070] Example 2

[0071] This embodiment provides a polyamide 66 resin and a preparation method thereof. The polyamide 66 resin includes the following components in parts by weight:

[0072] 100 parts of polyamide 66, 0.0001 parts of cuprous iodide, 0.0001 parts of light stabilizer 5591, 0.0005 parts of erucic acid amide and 0.0001 parts of hyperbranched polyamide polyester HyPer HPN202;

[0073] The polyamide 66 comprises the following raw material components in parts by weight:

[0074] 115 parts of polyamide 66 salt, 0.002 parts of potassium bicarbonate, 0.0002 parts of sodium hypophosphite and 0.0012 parts of acetic acid;

[0075] The preparation method of the polyamide 66 is as follows:

[0076] Potassium bicarbonate, sodium hypophosphite, acetic acid and water are mixed to obtain a mixed solution, and the mixed solution is mixed with polyamide 66 salt, concentrated at 150° C. and 0.25 MPa for 55 minutes, and then the pressure is increased to 1.80 MPa and maintained for 60 minutes. When the temperature of the reaction system reaches 267° C., at 60 minutes, the pressure of the reaction system is released to 0 MPa, and within 3 minutes, the reaction system is evacuated to -0.03 MPa. When the temperature of the reaction system reaches 273° C., the pressure is increased to 0.4 MPa to complete the polymerization reaction, and pelletized to obtain the polyamide 66; wherein the mass percentage of the first catalyst in the mixed solution is 15%, the mass percentage of the sodium hypophosphite is 1.5%, and the mass percentage of the acetic acid is 9%.

[0077] The preparation method of the above polyamide 66 resin is as follows:

[0078] The polyamide 66 resin is obtained by mixing polyamide 66, cuprous iodide, light stabilizer 5591, erucic acid amide and hyperbranched polyamide polyester HyPerHPN202 through a screw extruder and then pelletizing. The operating temperature of the screw extruder is 290°C.

[0079] Example 3

[0080] This embodiment provides a polyamide 66 resin and a preparation method thereof. The polyamide 66 resin includes the following components in parts by weight:

[0081] 100 parts of polyamide 66, 0.005 parts of copper bromide, 0.005 parts of light stabilizer 944, and 0.005 parts of stearyl erucamide;

[0082] The polyamide 66 comprises the following raw material components in parts by weight:

[0083] 115 parts of polyamide 66 salt, 0.0001 parts of sodium carbonate, 0.00004 parts of sodium hypophosphite and 0.0003 parts of acetic acid;

[0084] The preparation method of the polyamide 66 is as follows:

[0085] Sodium carbonate, sodium hypophosphite, acetic acid and water are mixed to obtain a mixed solution, and the mixed solution is mixed with polyamide 66 salt, concentrated at 150° C. and 0.25 MPa for 60 minutes, and then the pressure is increased to 1.85 MPa and maintained for 60 minutes. When the temperature of the reaction system reaches 265° C., the pressure of the reaction system is reduced to 0 MPa within 40 minutes, and then the reaction system is evacuated to -0.01 MPa within 10 minutes. When the temperature of the reaction system reaches 275° C., the pressure is increased to 0.6 MPa to complete the polymerization reaction, and pelletized to obtain the polyamide 66; wherein the mass percentage of the first catalyst in the mixed solution is 5%, the mass percentage of the sodium hypophosphite is 2%, and the mass percentage of the acetic acid is 15%.

[0086] The preparation method of the above polyamide 66 resin is as follows:

[0087] The polyamide 66 resin is obtained by mixing polyamide 66, copper bromide, light stabilizer 944 and stearyl erucic acid amide through a screw extruder and then pelletizing. The working temperature of the screw extruder is 320°C.

[0088] Example 4

[0089] This embodiment provides a polyamide 66 resin and a preparation method thereof. The polyamide 66 resin includes the following components in parts by weight:

[0090] 100 parts of polyamide 66, 0.0008 parts of Brueggemann H3386 stabilizer, 0.002 parts of Clariant TFB117 stabilizer, 0.001 parts of aluminum stearate and 0.005 parts of rice bran wax;

[0091] The polyamide 66 comprises the following raw material components in parts by weight:

[0092] 115 parts of polyamide 66 salt, 0.0009 parts of sodium bicarbonate, 0.00015 parts of sodium hypophosphite and 0.001 parts of acetic acid;

[0093] The preparation method of the polyamide 66 is as follows:

[0094] Sodium bicarbonate, sodium hypophosphite, acetic acid and water are mixed to obtain a mixed solution, and the mixed solution is mixed with polyamide 66 salt, concentrated at 155° C. and 0.25 MPa for 55 minutes, and then the pressure is increased to 1.85 MPa and maintained for 60 minutes. When the temperature of the reaction system reaches 267° C., the pressure of the reaction system is reduced to 0 MPa within 55 minutes, and then the reaction system is evacuated to -0.02 MPa within 6 minutes. When the temperature of the reaction system reaches 272° C., the pressure is increased to 0.3 MPa to complete the polymerization reaction, and pelletized to obtain the polyamide 66; wherein the mass percentage of the first catalyst in the mixed solution is 6%, the mass percentage of the sodium hypophosphite is 1%, and the mass percentage of the acetic acid is 6.67%.

[0095] The preparation method of the above polyamide 66 resin is as follows:

[0096] The polyamide 66 resin is obtained by mixing polyamide 66, Lugmann H3386 stabilizer, Clariant TFB117 stabilizer, aluminum stearate and rice bran wax through a screw extruder and then pelletizing. The operating temperature of the screw extruder is 300° C.

[0097] Example 5

[0098] This embodiment provides a polyamide 66 resin and a preparation method thereof. The difference from Embodiment 1 is that the raw materials for preparing the polyamide 66 do not contain sodium hypophosphite, the weight portion of acetic acid is 0.0011 parts, and other conditions are the same as those in Embodiment 1.

[0099] Example 6

[0100] This embodiment provides a polyamide 66 resin and a preparation method thereof. The difference from Embodiment 1 is that the raw material for preparing the polyamide 66 does not contain acetic acid, the weight portion of sodium hypophosphite is 0.0011 parts, and other conditions are the same as those in Embodiment 1.

[0101] Example 7

[0102] This embodiment provides a polyamide 66 resin and a preparation method thereof. The difference from Embodiment 1 is that the polyamide 66 resin does not contain copper acetate, the weight portion of Clariant TFB117 stabilizer is 0.005 parts, and other conditions are the same as those in Embodiment 1.

[0103] Example 8

[0104] This embodiment provides a polyamide 66 resin and a preparation method thereof. The difference from Embodiment 1 is that the polyamide 66 resin does not contain Clariant TFB117 stabilizer, the weight portion of copper acetate is 0.005 parts, and other conditions are the same as those in Embodiment 1.

[0105] Comparative Example 1

[0106] This comparative example provides a polyamide 66 resin and a preparation method thereof. The difference from Example 1 is that the raw material for preparing the polyamide 66 does not contain sodium bicarbonate, and the weight proportion of sodium bicarbonate is proportionally distributed to sodium hypophosphite and acetic acid. Other conditions are the same as those in Example 1.

[0107] Comparative Example 2

[0108] This comparative example provides a polyamide 66 resin and a preparation method thereof. The difference from Example 1 is that the raw materials for preparing the polyamide 66 do not contain sodium hypophosphite and acetic acid, the weight portion of sodium bicarbonate is 0.0021 parts, and other conditions are the same as those in Example 1.

[0109] The performance of the polyamide 66 resin provided in the above embodiments and comparative examples was tested, and the testing method was as follows:

[0110] Tensile strength: dumbbell-shaped tensile specimens were prepared using an injection molding machine, and the specimens were placed in an oven at 180°C for 72 hours. After cooling at room temperature for 24 hours, the tensile strength of the specimens was tested using a universal mechanical testing machine in accordance with the standard "GB / T 1040.1-2006 Determination of tensile properties of plastics".

[0111] Melt index: According to the standard of GB-T3682-Melt Flow Rate Determination, the melt index of the sample is tested using a melt index meter at 275°C and a weight of 2.16 kg.

[0112] Relative viscosity: According to the standard "GB / T 12006.1-2009 Plastics Polyamide Part 1: Determination of Viscosity", use Ubbelohde viscometer to test the relative viscosity of the sample.

[0113] Lubricity: Use an injection molding machine to test cable ties. The cable tie mold is 100 ties with a size of 5*150mm per mold. Record the average number of cable ties demoulded from each mold. The more ties there are, the better the lubricity.

[0114] Processability: When testing cable ties with an injection molding machine, record the highest processing temperature when the mold is full and has no overflow. The lower the temperature, the better the processability.

[0115] The performance test results of the polyamide 66 resin provided in the above examples and comparative examples are shown in Table 1 below:

[0116] Table 1

[0117]

[0118] As can be seen from the contents of Table 1, the present invention prepares a polyamide 66 resin with good high temperature resistance and lubricity through the selection of a specific catalyst, the combined use of a first catalyst and a second catalyst, and the combined use of a copper salt stabilizer and a hindered amine stabilizer, thereby improving the injection molding processing performance of the polyamide 66 resin. At 180°C, after heat treatment for 72 hours, its tensile strength can still be maintained at more than 80 MPa, which is 81.9-86.8 MPa; the melt index is greater than 87 g / 10min, which is 87-93 g / 10min; the relative viscosity can reach 2.66-2.67; the number of demolding roots is 85-100, and the maximum processing temperature is 280-285°C.

[0119] Compared with Example 1, if the catalyst system does not contain sodium hypophosphite (Example 5), the melt index and relative viscosity of the prepared polyamide 66 resin are relatively small, 79g / 10min and 2.51 respectively; if the catalyst system does not contain acetic acid (Example 6), the melt index of the prepared polyamide 66 resin is relatively small, 65g / 10min, the relative viscosity is too large, 2.75, and the maximum processing temperature is too high, 330°C. It can be seen that the polyamide 66 resin prepared by selecting a combination of sodium hypophosphite and acetic acid as the second catalyst in this application has excellent processing performance.

[0120] Compared with Example 1, if the polyamide 66 resin does not contain a copper salt stabilizer (Example 7), the high temperature resistance of the prepared polyamide 66 resin is poor; if the polyamide 66 resin does not contain a hindered amine stabilizer (Example 8), the high temperature resistance of the prepared polyamide 66 resin is poor, and the tensile strength is small after heat treatment at 180°C for 72 hours. It can be seen that there is a synergistic effect between the copper salt stabilizer and the hindered amine stabilizer, and the prepared polyamide 66 resin has excellent high temperature resistance through the combined use of the two.

[0121] Compared with Example 1, if the first catalyst sodium bicarbonate is not included in the catalytic system (Comparative Example 1), the melt index of the prepared polyamide 66 resin is as small as 70g / 10min, and the maximum processing temperature is too high at 330°C; if the second catalyst sodium hypophosphite and acetic acid are not included in the catalyst system (Comparative Example 2), the melt index of the prepared polyamide 66 resin is as small as 76g / 10min, and the maximum processing temperature is too high at 320°C. It can be seen that the polyamide 66 resin prepared by the combined use of the first catalyst and the second catalyst in the present application has excellent processing performance.

[0122] In summary, the polyamide 66 resin prepared by the present invention has good high temperature resistance, lubricity and fluidity,

[0123] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A polyamide 66 resin, characterized in that: The polyamide 66 resin comprises the following components in parts by weight: 100 parts of polyamide 66, 0.0002-0.01 parts of stabilizer and 0.0005-0.005 parts of lubricant; The polyamide 66 comprises the following raw material components in parts by weight: 115 parts of polyamide 66 salt, 0.0001-0.002 parts of the first catalyst and 0.00034-0.0014 parts of the second catalyst; The first catalyst is selected from any one or a combination of at least two of sodium bicarbonate, potassium bicarbonate or sodium carbonate; The second catalyst is a combination of sodium hypophosphite and acetic acid; The stabilizer is a combination of a copper salt stabilizer and a hindered amine stabilizer.

2. The polyamide 66 resin according to claim 1, characterized in that: The weight proportion of the sodium hypophosphite is 0.00004 to 0.0002 parts.

3. The polyamide 66 resin according to claim 1, characterized in that: The weight proportion of the acetic acid is 0.0003 to 0.0012 parts.

4. The polyamide 66 resin according to claim 1, characterized in that: The copper salt stabilizer is selected from inorganic copper salt stabilizers and / or organic copper salt stabilizers.

5. The polyamide 66 resin according to claim 4, characterized in that: The inorganic copper salt stabilizer is selected from any one of copper acetate, cuprous iodide, copper bromide or copper nitrate, or a combination of at least two thereof.

6. The polyamide 66 resin according to claim 4, characterized in that: The organic copper salt stabilizer is selected from any one of Brueggemann H3386 stabilizer, Brueggemann H3336 stabilizer or Brueggemann TP-H1606 stabilizer or a combination of at least two thereof.

7. The polyamide 66 resin according to claim 1, characterized in that: The hindered amine stabilizer is selected from any one of Clariant TFB117 stabilizer, light stabilizer 5591 or light stabilizer 944, or a combination of at least two thereof.

8. The polyamide 66 resin according to claim 1, characterized in that: The weight proportion of the copper salt stabilizer is 0.0001 to 0.005 parts.

9. The polyamide 66 resin according to claim 1, characterized in that: The weight portion of the hindered amine stabilizer is 0.0001 to 0.005 parts.

10. The polyamide 66 resin according to claim 1, characterized in that: The lubricant is selected from any one of oleamide, erucamide, stearyl erucamide, aluminum stearate, aluminum distearate, zinc stearate or magnesium stearate, or a combination of at least two thereof.

11. The polyamide 66 resin according to claim 1, characterized in that: The polyamide 66 resin further includes 0.0001 to 0.005 parts of a fluidity improver.

12. The polyamide 66 resin according to claim 11, characterized in that: The fluidity improver is selected from any one of ethylene bis stearic acid amide, hyperbranched polyamide polyester HyPer HPN202, montan wax or rice bran wax, or a combination of at least two thereof.

13. The polyamide 66 resin according to claim 1, characterized in that: The preparation method of polyamide 66 is as follows: The first catalyst and the second catalyst are mixed with water to obtain a mixed solution, and the mixed solution is mixed with polyamide 66 salt to carry out a polymerization reaction to obtain polyamide 66.

14. The polyamide 66 resin according to claim 13, characterized in that: The mass percentage of the first catalyst in the mixed solution is 5-15%.

15. The polyamide 66 resin according to claim 13, characterized in that: The mass percentage of the second catalyst in the mixed solution is 5% to 20%.

16. The polyamide 66 according to claim 13, characterized in that The specific method of the polymerization reaction is as follows: Under the conditions of 150-155°C and 0.25MPa, the reaction system after mixing the mixed liquid and polyamide 66 salt is concentrated for 50-60min, then the pressure is increased to 1.75-1.85MPa and the pressure is maintained for 50-60min. When the temperature of the reaction system reaches 265-267°C, the pressure of the reaction system is released to 0MPa within 40-60min, and the reaction system is evacuated to -0.01-0.03MPa within 2-10min. When the temperature of the reaction system reaches 270-275°C, the pressure is increased to 0.2-0.6MPa, thus completing the polymerization reaction and obtaining the polyamide 66.

17. A method for preparing a polyamide 66 resin according to any one of claims 1 to 12, characterized in that: The preparation method comprises the following steps: The polyamide 66 resin is obtained by mixing polyamide 66 with a stabilizer, a lubricant and an optional fluidity improver through a screw extruder and then pelletizing.

18. The preparation method according to claim 17, characterized in that: The operating temperature of the screw extruder is 265-320°C.

Citation Information

Patent Citations

  • Ultra-high toughness polyamide 66 material and preparation thereof

    CN101440215A

  • Halogen-free environmentally friendly flame-proof enhanced nylon 66 resin and preparation method thereof

    CN101608065A

  • Hydrolysis-resistant alcoholysis-resistant nylon 66 composite material and preparation method thereof

    CN102516761A

  • Polyamide resin as well as preparation method and application thereof

    CN110437445A

  • Thermoplastic melt-mixed composition with heat stabilizer

    US20120196962A1